If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(-1x + 4) = 15 Reorder the terms: 9(4 + -1x) = 15 (4 * 9 + -1x * 9) = 15 (36 + -9x) = 15 Solving 36 + -9x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + -9x = 15 + -36 Combine like terms: 36 + -36 = 0 0 + -9x = 15 + -36 -9x = 15 + -36 Combine like terms: 15 + -36 = -21 -9x = -21 Divide each side by '-9'. x = 2.333333333 Simplifying x = 2.333333333
| 4y-2=4y+2 | | 0.3w-4=.8-.2w | | 5+2qrstx=9 | | .75-9p=-0.6 | | 5/14=-2a/7 | | 50b+2.25=1.75 | | -3+2w+5.67-2.44w= | | 5/14=-2e/7 | | 5(3b^2-2b)+10b^2-1= | | -3k^2-7k=0 | | 3x=7x+12 | | 18(x-3)=19 | | -x^2+8x-2=0 | | 8+5x=33 | | ex=7x+12 | | 4-2x=12+6x | | 2w-3(w)-65=0 | | 5(3b*2-2b)+10b*2-1= | | 4(-2-3X)=[-6X-5(8-6X)] | | (4x^3)-(36x^2)+(96x)-(64)=0 | | 4.571428571a^2=1-7.428571429a | | x^2+38x+13= | | 5x+3y=63 | | 150+20x=150+15x | | (2x+3)(2x-6)=y | | 33+4y-1=12y-10-2y | | -100r^2+1=0 | | -7+10z+2.1-7z= | | 5(3b*3b-2b)= | | -x^3+5x^2+104x= | | a+6b=6 | | 3(4*8)+(85/3)-(6+3*4)= |